Francophonie en Orient Aux Croisements France-Asie (1840-1940) - Kang, Mathilde (Languages and culture in history., 2018)
This book offers a pioneering study of Asian cultures that officially escaped from French colonization but nonetheless were steeped in French civilization in the colonial era and had heavily French-influenced, largely francophone literatures. It raises a number of provocative questions, including whether colonization is the ultimate requirement for a culture's being defined as francophone, or how to think about francophone literatures that emerge from Asian nations that were historically free from French domination. The ultimate result is a redefining of the Asian francophone heritage according to new, transnational paradigms.